Implementasi Model Make a Match Berbantuan Media Pocket Book untuk Meningkatkan Aktivitas Pembelajaran IPA - Nining Sariyyah; Adi Neneng Abdullah (Journal on Education, 2023)
This study aims to improve science learning activities in grade IV SDK St Ambrosius Ende 6. This research is a classroom action research. the research object consisted of 20 grade IV students. Data were collected by observation techniques, field notes and interviews. The data were analyzed by simple descriptive statistics to determine the percentage increase in student learning activities and their categories for each cycle. The results showed that after implementing the make a match model with the help of pocket book media, there was an increase in student learning activity from cycle I by 49% with the moderately active category to 91% in cycle II with the very active category. Thus, the make a match model with the help of pocket book media can increase the learning activities of class IV SDK St Ambrose Ende 6.